Flight performance and trajectory prediction of a 2.75-inch solid propellant rocket - Hamlan, Nur Syahirah Shafek; Gires, Ezanee; Ahmad, Kamarul Ariffin; Mustapha, Faizal; Mazlan, Norkhairunnisa; Yidris, Noorfaizal; Basri, Adi Azriff (Springer Science and Business Media, 2024)
The flight performance and flight trajectory of any unguided rocket should be determined because its capability and flight trajectory are uncountable in flights. The purpose in this study was to develop a performance and trajectory prediction program for an unguided 2.75-inch solid propellant rocket and to perform a parametric analysis. The program uses the Runge–Kutta Fehlberg (or RKF45) method, and it was developed using Python. It requires multiple geometric designs and motor parameters as the program input. The program was then verified and validated with previous experimental flight data obtained from literature papers. Then, a parametric analysis (also called as sensitivity analysis) was done to analyze how significant these parameters affect the flight of a rocket, compared with the results based on the baseline rocket. Based on the prediction results, the baseline rocket flies with a range of 3040 m, reaches up to 3307 m in altitude and has a peak velocity of 747.554 m/s. In parametric analysis, the parameter that gave the most significant difference was motor grain configuration, followed by launch angle and nozzle expansion ratio.